2017
DOI: 10.1088/1361-665x/aa8aa4
|View full text |Cite
|
Sign up to set email alerts
|

Low power consumption mini rotary actuator with SMA wires

Abstract: Shape memory alloys (SMAs) are smart materials widely used as actuators for their high power to weight ratio despite their well-known low energy efficiency and limited mechanical bandwidth. For robotic applications, SMAs exhibit limitations due to high power consumption and limited stroke, varying from 4% to 7% of the total length. Hysteresis, during the contraction and extension cycle, requires a complex control algorithm. On the positive side, the small size and low weight are eminently suited for the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Our ambient RF survey has clearly shown the possibility of efficiently utilizing ambient RF energy harvesting for powering the MEMS-based embedded sensors and actuators in different materials or membranes. A recently reported (16) low-power-consumption rotary actuator can be efficiently powered by this widely available ambient RF energy. These RF powered MEMS-based embedded devices can be part of a telemetry system whereby they remotely measure some physical parameters and send the information back to a central processing center for further action.…”
Section: Resultsmentioning
confidence: 99%
“…Our ambient RF survey has clearly shown the possibility of efficiently utilizing ambient RF energy harvesting for powering the MEMS-based embedded sensors and actuators in different materials or membranes. A recently reported (16) low-power-consumption rotary actuator can be efficiently powered by this widely available ambient RF energy. These RF powered MEMS-based embedded devices can be part of a telemetry system whereby they remotely measure some physical parameters and send the information back to a central processing center for further action.…”
Section: Resultsmentioning
confidence: 99%
“…Now, applying Eqs. (3)(4)(5)(6) to (2), the resistance due to hoop stress can be written as Table 1 Physical parameters of the pig small intestine (adopted from [28])…”
Section: Resistancesmentioning
confidence: 99%
“…To design a locomotive mechanism for such a small capsule is a challenging task due to its limited on-board space. Smart materials [2] and small-scale DC motors have been used to address this issue. For example, a CE with three active flexible legs controlled by means of an on-board microcontroller was constructed by using shape memory alloy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Limitation in the mechanical bandwidth has been reported for large applications because of the slow time required to dissipate the accumulated heat. In recent studies, Manfredi et al [26][27][28][29] reported high mechanical bandwidth for the design of a mini actuator with thin SMA wires, 75µm and 100µm in diameter. Legged MRC has been designed by using SMA [30].…”
Section: On-board Locomotionmentioning
confidence: 99%